'Metal free' fluorescent anionic assemblies: Efficient platform for detection of electron deficient nitroaromatics and cationic dyes. (December 2019) - Kataria, Meenal; Singh, Zujhar; Kumar, Manoj; Bhalla, Vandana
Abstract: Supramolecular assemblies of cyclopentadienone derivative3 exhibit cyanide induced emission enhancement and undergo modulation of self-assembled structure to generate 'metal free' supramolecular porous anionic assemblies. The as prepared anionic assemblies show high sensitivity and selectivity for the detection of picric acid among various nitro-derivatives tested in aqueous media and in vapour phase. Further, due to the porous nature, the anionic ensemble selectively detects cationic dyes such as methylene blue among various dyes tested in aqueous media. Graphical abstract: Assemblies of cyclopentadienone derivative 3 exihibited cyanide induced emission enhancement and undergo cyanide induced modulation of self-assembled structure to generate 'metal free' supramolecular porous anionic assemblies The as preapred anionic assemblies showed high senstivity and selectivity for the detection of picric acid and cationic dyes in aqueous media.Image 1 Highlights: Focused on the preparation of 'metal free' anion centered assemblies in aqueous media. We developed polymeric supramolecular anionic assemblies having multiple anion binding sites that can encapsulate cyanide ion in mixed aqueous media. The sensing response of supramolecular ensemble3-CN - for picric acid in aqueous media is also better/ comparable than other reported system in literature. These anionic assemblies also exhibited selective response towards cationic dyes and could discriminate between methylene blue and crystal violet cationic dye due to their different size and shape. The supramolecular anionic ensemble was also utilized for the separation of mixture of cationic and anionic dyes by using the coloumn chromatography. Moreover, this is the first report of utilization of 'metal free' anionic assemblies in aqueous media for the discriminative sensing of cationic dyes.